Multi-omics analysis reveals regulators of the response to nitrogen limitation in Yarrowia lipolytica. (December 2016) - Pomraning, Kyle; Kim, Young-Mo; Nicora, Carrie; Chu, Rosalie; Bredeweg, Erin; Purvine, Samuel; Hu, Dehong; Metz, Thomas; Baker, Scott
Abstract Background Yarrowia lipolytica is an oleaginous ascomycete yeast that stores lipids in response to limitation of nitrogen. While the enzymatic pathways responsible for neutral lipid accumulation inY. lipolytica are well characterized, regulation of these pathways has received little attention. We therefore sought to characterize the response to nitrogen limitation at system-wide levels, including the proteome, phosphoproteome and metabolome, to better understand how this organism regulates and controls lipid metabolism and to identify targets that may be manipulated to improve lipid yield. Results We found that ribosome structural genes are down-regulated under nitrogen limitation, during which nitrogen containing compounds (alanine, putrescine, spermidine and urea) are depleted and sugar alcohols and TCA cycle intermediates accumulate (citrate, fumarate and malate). We identified 1219 novel phosphorylation sites inY. lipolytica, 133 of which change in their abundance during nitrogen limitation. Regulatory proteins, including kinases and DNA binding proteins, are particularly enriched for phosphorylation. Within lipid synthesis pathways, we found that ATP-citrate lyase, acetyl-CoA carboxylase and lecithin cholesterol acyl transferase are phosphorylated during nitrogen limitation while many of the proteins involved in β-oxidation are down-regulated, suggesting that storage lipid accumulation may be regulated by phosphorylation of key enzymes. Further, we identified short DNA elements that associate specific transcription factor families with up- and down-regulated genes. Conclusions Integration of metabolome, proteome and phosphoproteome data identifies lipid accumulation in response to nitrogen limitation as a two-fold result of increased production of acetyl-CoA from excess citrate and decreased capacity for β-oxidation.